As formações discursivas sobre o "Ser Surdo" na Escola Inclusiva - Oliveira, Sebastião Reis de (2017)
This dissertation addresses the discursive formations on being deaf in the inclusive school. The theoretical reference was that of the French discourse analysis circumscribed in the category of discursive formation. The idea to present this theme is justified by the experiences acquired and experienced as a professional translator / interpreter of Libras in one of the schools where the research was carried out, as well as by the emergence of this category of inclusive education concomitant with legal advances in the context of Brazilian democratization Since 1988 in order to verify the concrete pertinence of this category in the light of the discourse theory by peering at the official discourses of strata and social classes agents of these practices of inclusive education of the deaf. The general objective was to analyze the discourse about discursive formations elaborated by teachers, hearing students and deaf students about the "deafness" in the inclusive school and, as specific, to investigate the reality of the deaf students in the inclusive school; To analyze the discursive formations elaborated by the teachers in relation to the deaf student in the inclusive school; To analyze the discursive formations elaborated by the hearing students in relation to the deaf student in the inclusive school; To analyze the discursive formations elaborated by the deaf students regarding the inclusive school. The methodology was qualitative because it was a research about the efficacy of the discourse regarding social phenomenon and the field research was that of participant because the deaf and hearing students and teachers lived together with the studied subjects. Keywords: inclusive education; deaf student; discourse analysis; discursive formation.